Determinants of postnatal care service utilization among married women in rural areas in western Ethiopia - Tesfalidet Beyene; Alemu Sufa Melka; Birhanu Yadecha (BMC, 2022)
Abstract Background Worldwide studies have shown that three-fourths of the total deaths during the neonatal period occur in the first week of the postnatal period. However, most of these deaths can be prevented with care during pregnancy, childbirth, and postnatal care. According to the 2016 Ethiopia Demographic and Health Survey report, 17% of women in Ethiopia had received postnatal care after childbirth. This study aimed to identify determinants of postnatal care service utilization among married women in rural areas in Western Ethiopia. Methods A community-based cross-sectional study was conducted among 798 women who had given birth in the past 2 years prior to the survey between 2 and 31 January 2015. A pre-tested structured questionnaire was used to collect the data. Multivariable logistic regression was employed to determine factors affecting utilization of postnatal care. Adjusted odds ratios (AOR) and 95% confidence intervals (CI) were used to assess the strength of the associations. Results The study showed that 188 (23.6%) women utilized postnatal care services during their last pregnancy. Women's educational level (AOR = 3.29, 95%CI = 1.89-5.73), utilization of antenatal care (AOR = 2.07, 95%CI = 1.28-3.36), awareness on the advantage of postnatal care (AOR = 2.10, 95%CI = 1.41-3.13), and knowledge of at least one danger sign during the postnatal period (AOR = 3.04, 95%CI = 2.07-4.46) showed a significant positive association with the utilization of postnatal care. Conclusion Educating women and creating awareness of maternal health care services during pregnancy increase the utilization of postnatal care services. Health care professionals should provide information on the importance of postnatal care for pregnant women during antenatal care visits.